2010
DOI: 10.4103/0970-4388.76157
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of various root canal irrigants on removal of smear layer in the primary root canals after hand instrumentation: A scanning electron microscopy study

Abstract: The results of the present study clearly indicate the superior efficacy of 6% citric acid than the other tested irrigants on removing the smear layer in primary teeth root canals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 13 publications
2
40
0
5
Order By: Relevance
“…Despite high success rates previously presented 2,4–10,12,13 , the effect of smear layer removal on primary teeth pulpectomies outcome has not been well elucidated. The choice of 6.0% citric acid as the final irrigation agent for smear layer removal was based on previous, in vitro 15,16 , and clinical 2,13 studies in primary teeth. Citric acid presents the best efficacy for smear layer removal in the primary root canals without altering the normal dentinal structures 16 and is less cytotoxic 26 than EDTA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite high success rates previously presented 2,4–10,12,13 , the effect of smear layer removal on primary teeth pulpectomies outcome has not been well elucidated. The choice of 6.0% citric acid as the final irrigation agent for smear layer removal was based on previous, in vitro 15,16 , and clinical 2,13 studies in primary teeth. Citric acid presents the best efficacy for smear layer removal in the primary root canals without altering the normal dentinal structures 16 and is less cytotoxic 26 than EDTA.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of 6.0% citric acid as the final irrigation agent for smear layer removal was based on previous, in vitro 15,16 , and clinical 2,13 studies in primary teeth. Citric acid presents the best efficacy for smear layer removal in the primary root canals without altering the normal dentinal structures 16 and is less cytotoxic 26 than EDTA. Furthermore, the occurrence of enamel with white opacities in the successor dentition after primary tooth pulpectomy with and without a 6% citric acid solution was low and similar in both groups, emphasizing that the usage of 6% citric acid is not related to damage to the successor dentition 2 .…”
Section: Discussionmentioning
confidence: 99%
“…24,25 though smear layer removal was better when EDtA was used in combination with sodium hypochlorite damage to the dentinal tubules, peritubular dentin erosion and disruption of intertubular dentin was found. 17 Studies have shown irrigation with 6% CA for 15 or 30 seconds is quite effective in removing all the components of the smear layer of the primary teeth whereas peritubular dentin destruction was observed when higher concentration of CA was used as an irrigating solution.…”
Section: Ethylenediaminetetraacetic Acid and Citric Acidmentioning
confidence: 99%
“…15,16 A study compared saline and NaOCl in its ability to remove smear layer in primary teeth which showed NaOCl was better than saline, although it partially removes smear layer. 17 Another study showed when 6.0% CA is used in association with hypochlorite as auxiliary chemical substances for irrigating primary teeth has remarkable effect on smear layer removal of primary molars. 18 though NaOCl is a commonly used root canal irrigant, it has an unpleasant odor and taste; it does not consistently disinfect the root canal system and is toxic when extruded into the periradicular tissues.…”
Section: Sodium Hypochloritementioning
confidence: 99%
“…Diffusion of OHˉ raises the pH 7,13) , destroying bacteria and inactivating their enzymes, while that of Ca 2+ reduces osteoclastic activity and activates alkaline phosphatase, which is involved in tissue re-mineralization 4) . A 17% EDTA solution is a common choice in treating root canals in primary teeth 1,11) . However, few studies have investigated its efficacy and applicability in conjunction with calcium hydroxide in the endodontic treatment of these teeth.…”
Section: Introductionmentioning
confidence: 99%